Electronics method to advance the coincidence time resolution with bismuth germanate. (5th September 2019) - Cates, Joshua W; Levin, Craig S
Abstract: Exploiting the moderate Cherenkov yield from 511 keV photoelectric interactions in bismuth germanate (BGO) scintillators enables one to achieve a level of coincidence time resolution (CTR) appropriate for time-of-flight positron emission tomography (TOF-PET). For this approach, owing to the low number of promptly emitted light photons, single photon time resolution (SPTR) can have a stronger influence on achievable CTR. We have previously shown readout techniques that reduce effective device capacitance of large area silicon photomultipliers (SiPMs) can yield improvements in single photon response shape that minimize the influence of electronic noise on SPTR. With these techniques, sub-100 ps FWHM SPTR can be achieved with mm 2 FBK near-ultra-violet high density (NUV-HD) SiPMs. These sensors are also useful for detecting Cherenkov light due to relatively high photon detection efficiency for UV light. In this work, we measured CTR for BGO crystals coupled to FBK NUV-HD SiPMs with a passive bootstrapping readout circuit that effectively reduces the SiPM device capacitance. A range of CTR values between 200 3 and 277 7 ps FWHM were measured for 3 3 3 and 3 3 15 mm 3 crystals, respectively. This readout technique provides a relatively simple approach to achieve state-of-the-art CTR performance using BGO crystals for TOF-PET.